Mesopredator release and the effectiveness of camera traps for estimating mammal abundances in the Eastern Cape, South Africa - Taylor, Jonathan Michael (Rhodes University, Faculty of Science, Department of Ichthyology and Fisheries Science, 2016)
Remotely operated cameras (camera traps) have become an indispensable tool for many ecologists, particularly those studying rare and elusive animals. A plethora of camera trap makes and models are now commercially available, yet the effects of their varying design features on the quality and quantity of data recorded remains principally unknown. Better understanding of differing camera trap designs is needed before adequate management policies can be implemented, especially when the aim is to protect vulnerable and endangered species such as many carnivores. Habitat loss and human conflict has prompted worldwide declines of apex predator populations. Following this, many smaller predators have undergone population 'explosions' due to the lack of top-down forcing, a phenomenon known as mesopredator release. Land use changes in the Eastern Cape of South Africa have caused extensive degradation and fragmentation of the Subtropical Thicket Biome. In addition, coupled with anthropogenic persecution, apex predators including lions (Panthera leo), leopards (P. pardus), and brown hyaenas (Hyaena brunnea) have been extirpated from large areas of their historic range. Removal of these apex predators may provide opportunity for mesopredators, such as black-backed jackals (Canis mesomelas) and caracals (Caracal caracal), to be released from top-down forcing and possibly initiate trophic cascade effects. Therefore, using randomly distributed camera traps, my study aimed to explore the quality and quantity of data collected by different camera trap designs, and to investigate the mesopredator release hypothesis in the Eastern Cape of South Africa. A total of 2,989 trap nights was used to compare camera trap designs. Camera traps with narrow detection zones and fast trigger speeds (â‰¤ 0.25 seconds) recorded a higher diversity of carnivores, but there was no significant difference in the relative abundances of carnivore species recorded by different camera trap models. A total of 19,659 trap nights was used to assess mesopredator relative abundance, occupancy, distribution and daily activity patterns at one site with, and one site without, apex predators. Consistent with the mesopredator release hypothesis, black-backed jackal relative abundance was significantly higher in the absence of apex predators, and this was supported by occupancy analyses. Further, black-backed jackal distribution was significantly concentrated in areas where apex predator activity was low, possibly indicating spatial avoidance. There was no significant difference in caracal relative abundance, occupancy, distribution, or daily activity between sites. These results provide the first indication of mesopredator release of blackbacked jackals in the Eastern Cape. The implications of black-backed jackal release including prey population structure, local extinctions, altered seed dispersal and disease dynamics are discussed.
Keywords: Uncatalogued